Protocol for decellularizing and delipidizing human pancreatic tissue into native hydrogel - Connie S. Chamberlain; Daniel M. Tremmel; Ayesha Palwasha Khan; Ellen Abad Santos; Deep Kapadia; Caterra Leavens; Katherine M. Gorski; Rawan Hamadeh; Austin K. Feeney; Jon Odorico; Sara D. Sackett (STAR Protocols, 2025)
Summary: We present a protocol for transforming human pancreatic tissue into a decellularized and delipidized extracellular matrix (ECM) for hydrogel/scaffold applications. We describe steps for decellularization and delipidization using sodium deoxycholate and sequential ethanol, acetone, and hexane washes and removal of nucleic acids with benzonase. We then detail procedures for lyophilizing the ECM for long-term preservation and digesting the pancreatic ECM in pepsin-HCL to form a hydrogel.For complete details on the use and execution of this protocol, please refer to Tremmel et al.1 and Sackett et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.